2020
DOI: 10.5055/jom.2020.0559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical manipulation on the oral pharmacokinetic profile of Xtampza® ER (oxycodone DETERx® formulation): A review of published studies

Abstract: Opioids can be an effective treatment option for appropriate patients with chronic pain for whom nonpharmacological or nonopioid treatment does not provide adequate pain relief. However, extended-release (ER) opioid formulations, because of their high drug content, are attractive options for nonmedical use and abuse. Xtampza® ER (oxycodone DETERx®) capsules, an ER abuse-deterrent formulation (ADF), contain microspheres that combine oxycodone with inactive ingredients to increase the difficulty of tampering wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…ER opioid analgesics are indicated for the treatment of severe and persistent pain that requires an extended treatment period for which alternative pain management options are inadequate. [26][27][28][29] ER opioids have shown safety and efficacy in clinical trials for the control of various chronic pain conditions. [30][31][32][33] However, ER formulations typically have higher levels of active drugs that are appealing for nonmedical use and abuse and are therefore susceptible to abuse through tampering or swallowing multiple tablets.…”
Section: Pain Management and Risk Of Oudmentioning
confidence: 99%
See 2 more Smart Citations
“…ER opioid analgesics are indicated for the treatment of severe and persistent pain that requires an extended treatment period for which alternative pain management options are inadequate. [26][27][28][29] ER opioids have shown safety and efficacy in clinical trials for the control of various chronic pain conditions. [30][31][32][33] However, ER formulations typically have higher levels of active drugs that are appealing for nonmedical use and abuse and are therefore susceptible to abuse through tampering or swallowing multiple tablets.…”
Section: Pain Management and Risk Of Oudmentioning
confidence: 99%
“…[30][31][32][33] However, ER formulations typically have higher levels of active drugs that are appealing for nonmedical use and abuse and are therefore susceptible to abuse through tampering or swallowing multiple tablets. 25,26 The Research Abuse, Diversion and Addiction-Related Surveillance (RADARS) system found that prescription-adjusted rates of abuse and diversion (defined as an instance of unlawful channeling of a product of interest from legal sources that results in a written report or complaint) for ER opioids were 2.8-fold and 2.1-fold higher, respectively, than IR opioids. 34 This may be due to high-risk patients preferring to abuse ER medication.…”
Section: Pain Management and Risk Of Oudmentioning
confidence: 99%
See 1 more Smart Citation
“…Xtampza ER ® (Collegium Pharmaceutical Inc.) is an ER ADF of oxycodone, which was approved by the FDA in 2016. Xtampza ER ® is a microsphere-in-capsule formulation using the proprietary DETERx ® technology that makes it less susceptible to manipulation using a variety of tools and solvents relative to IR oxycodone tablets [69]. Brennan et al [70] reported that after oral administration of crushed IR oxycodone, a rapid increase in oxycodone concentration was observed.…”
Section: Drug Formulations To Improve Safetymentioning
confidence: 99%
“…Premarket in vitro and in vivo testing of Xtampza ER is well documented and demonstrates the difficulties in manipulating the product as well as the product's pharmacokinetic profile and human abuse potential. [7][8][9][10][11][12][13][14] Published postmarket data is limited to a recent publication comparing Xtampza ER to IR oxycodone, other ADF ER opioids, and non-ADF ER opioids which suggested that Xtampza ER has low relative abuse rates and low relative likelihood of non-oral use. 15 While these results were consistent across several data sources, additional real-world data are needed to further understand the relative risk of abuse of currently available opioid medications.…”
Section: Introductionmentioning
confidence: 99%